The anti-inflammatory effects of low- and high-molecular-weight beta-glucans from Agrobacterium sp. ZX09 in LPS-induced weaned piglets. Issue 1 (20th December 2019) - Luo, Junqiu; Cheng, Long; Du, Yanjun; Mao, Xiangbing; He, Jun; Yu, Bing; Chen, Daiwen
Abstract : The physicochemical characteristics of beta-glucans determine the immune responses of the intestines and system. Abstract : The physicochemical characteristics of beta-glucans determine the immune responses of the intestines and whole body. It is hypothesized that glucans with different molecular weights have diverse modes of action on LPS-mediated immune activity. This study aimed to verify the immune-modulatory effects of two types of beta-glucans in LPS-induced weaned piglets. The results indicated that dietary beta-glucan supplementation could prevent losses in body weight gain caused by LPS challenge. Supplementation with different molecular weights of beta-glucans decreased the production of IL-1β and TNF-α and increased IL-10 production, which is likely associated with key factors such as TLR4 and NF-κB. High-molecular-weight beta-glucans seemed to have a strong functional capacity to modulate the innate immune response through the Dectin-1 receptor. Therefore, the results indicate that supplementing piglets with Agrobacterium sp. ZX09 beta-glucans inhibits LPS-mediated depression in the growth performance and plays a protective role during LPS challenge possibly via the Dectin-1 receptor and the TLR4/NF-κB pathway. The results reveal the potential therapeutic activity of purified Agrobacterium sp. ZX09 beta-glucan following experimental LPS infusion.